2012
DOI: 10.3892/ijo.2012.1336
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of Cdc42 in lung cancer and modulation of its expression by curcumin in lung cancer cell lines

Abstract: Abstract. Cdc42, a Rho GTPase family member, is involved in cell transformation, proliferation, survival, invasion and metastasis of human cancer cells. Overexpression of Cdc42 has been reported in several types of human cancer. However, the underlying mechanisms are not well understood. The present study showed that Cdc42 was overexpressed in 80 of 110 primary lung cancer patients, and overexpression of Cdc42 was significantly associated with high TNM stage and lymph node metastasis. Moreover, RNAi-mediated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 27 publications
(35 reference statements)
1
45
0
1
Order By: Relevance
“…Consistent with its important functions in these distinct physiological and pathological processes, abnormal expression of CDC42 has been identified in numerous diseases, particularly in human cancer. CDC42 has been identified to be upregulated in a number of human cancers, including lung cancer (44). Therefore, it may be advantageous to investigate novel targeted therapy against CDC42 in lung cancer.…”
Section: Cdc42 Is Involved In Mir29a-induced Effects In Nsclc Cellsmentioning
confidence: 99%
“…Consistent with its important functions in these distinct physiological and pathological processes, abnormal expression of CDC42 has been identified in numerous diseases, particularly in human cancer. CDC42 has been identified to be upregulated in a number of human cancers, including lung cancer (44). Therefore, it may be advantageous to investigate novel targeted therapy against CDC42 in lung cancer.…”
Section: Cdc42 Is Involved In Mir29a-induced Effects In Nsclc Cellsmentioning
confidence: 99%
“…For instance, Chen and colleagues reported the effect of curcumin to prevent cancer progression and metastasis using an in vivo lung cancer model. In this work, it was demonstrated that curcumin downregulated the expression of Cdc42 and Rho GTPase protein that plays an important role in proliferation, invasion and metastasis [245]. In fact, several studies have associated the overexpression of Cdc42 and the progression of a variety of human cancers [246].…”
Section: Metastasismentioning
confidence: 99%
“…Overwhelmingly, mechanisms of action reported for the antitumor efficacy of curcumin in lung cancer cells are via mitochondrial-mediated cell death elicited by an increase in the Bax:B cell lymphoma-2 ratio or by an increase in intracellular reactive oxygen species (ROS) (Chanvorachote et al, 2009;Pongrakhananon et al, 2010;Saha et al, 2010;Wu et al, 2010;Wang et al, 2011Wang et al, , 2013bSahoo et al, 2012;Yang et al, 2012a,b;Liu et al, 2013;Xiao et al, 2013;Chen et al, 2014). Migration and invasive capacity of lung cancer cells may be further decreased by inhibition of matrix metalloprotease expression, decreased nuclear factor-kB, EGFR, Akt, signal transducer and activator of transcription 3, and Cdc42 signaling (Chen et al, 2004(Chen et al, , 2012Lee et al, 2005;Lin et al, 2009Lin et al, , 2012Puliyappadamba et al, 2010;Kaushik et al, 2012;Liu et al, 2013;Yamauchi et al, 2014;Zhou et al, 2013a;Li et al, 2014b). Although drug resistance in lung cancer is a primary cause for therapeutic failure, very few in vitro models of resistance have been used when investigating the potential of curcumin for tertiary interventional strategies.…”
Section: Models For Tertiary Lung Cancer Preventionmentioning
confidence: 99%